The impact of red blood cell transfusion on mortality and treatment efficacy in patients treated with radiation: A systematic review. (March 2022) - Deschner, Max; Vasanthamohan, Lakshman; Zayed, Sondos; Lazo-Langner, Alejandro; Palma, David; D'Souza, David; Omar Gilani, Syed; Gabriel Boldt, R.; Solh, Ziad
Graphical abstract: Highlights: Higher hemoglobin (Hb) levels may improve outcomes in radiation therapy (RT). There are no standard red blood cell transfusion thresholds for RT patients. We found no differences between standard and higher Hb thresholds during RT. Data is lacking on the effects of transfusion strategies in patients undergoing RT. Abstract: Introduction: Packed red blood cell (RBC) transfusion is frequently used in patients undergoing radiotherapy (RT) because retrospective data suggest that anemic patients may respond sub-optimally to RT. No high-quality evidence currently exists to guide transfusion practices and establish hemoglobin (Hb) transfusion thresholds for this patient population, and practice varies significantly across centers. This systematic review investigated whether maintaining higher Hb via transfusion in radiation oncology patients leads to improved outcomes. Methods: We performed a literature search of studies comparing RBC transfusion thresholds in radiation oncology patients. Included studies assessed patients receiving RT for malignancy of any diagnosis or stage. Excluded studies did not evaluate Hb or transfusion as an intervention or outcome. The primary outcome was overall survival. Secondary outcomes included locoregional control, number of transfusions and adverse events. Results: One study met inclusion criteria. The study pooled results from two randomized controlled trials that stratified anemic patients with head and neck squamous cell carcinoma to RBC transfusion versus no transfusion. The study found no significant differences in overall survival or locoregional control after five years, despite increased Hb levels in the transfused group. We conducted a narrative review by extracting data from 10 non-comparative studies involving transfusion in patients receiving RT. Results demonstrated no consistent conclusions regarding whether transfusions improve or worsen outcomes. Conclusions: There is a lack of data on the effects of RBC transfusion on outcomes in patients undergoing RT. Well-designed prospective studies are needed in this area.